ANALISIS PERBANDINGAN PENGUKURAN KINERJA KEUANGAN, DAN ANALISIS TREN ANTARA BANK SYARIAH DAN BANK KONVENSIONAL - mulia saputra; Nadirsyah Nadirsyah; Muhammad Khaidir (JURNAL EKOMBIS, 2020)
The this study tries to examined and compare the performance of sharia and conventional banking in Indonesia during and after global financial crisis period of 2013-2018 and analyzing which of the banking stream is performing better than other. There are 6 sample of each banks have been selected. The measurement use for comparing the performance of those banking includes the differences of profitability, liquidity, solvency and business development. There are eleventh financial ratios were involved to measure the ration of profitability, liquidity and solvency. However, other tools such as trend analysis are also applied to observe the trends of profit/loss statement and balance sheet. Findings suggest the profitability ratio of two banks, within global crisis Islamic banks leads, while after global crisis conventional banks boast its performance. In term of liquidity conventional banks leads Sharia banks during and after global financial crisis, while in solvency maintenance Sharia banking dominates during global crisis and they have same performance after global crisis. In business development, sharia banks more develop than conventional during and after global financial crisis. Another finding, there is a trend analysis which infers the sharia banks have good trend of balance sheet while in profit/loss statements there is no meaningful gap.Keywords: Financial measurement, Business Development, Trend Analysis, Sharia Banks, Conventional Banks